New veterinary medicinal products authorised by centralised procedure - Simona Sturzu (Medicamentul Veterinar)
Veterinary medicinal products that are subject to authorization via the centralized procedure according to Regulation (EC) no. 726/2004 are included in the Community register of veterinary medicines, that is published on the European Commission website and product information of them are published on the website of the European Medicines Agency. Each competent authority involved in the linguistic review process of product information annexed to the Marketing Authorization for medicinal products authorized centrally (SPC, leaflet, information about the marketing authorization holder, product labeling conditions), approve the version in the language mother of each Member State. In the second half of 2011 have received marketing authorization via the centralized procedure a total of four veterinary medicinal products, presented above.